2011
DOI: 10.1510/icvts.2010.251538
|View full text |Cite
|
Sign up to set email alerts
|

Cell saving systems do not reduce the need of transfusion in low-risk patients undergoing cardiac surgery

Abstract: In low-risk patients CS system did not reduce the need of blood transfusion. Clinical outcomes were similar regardless of the use of a cell saver system. A low preoperative hemoglobin level and a low BSA were related with the use of blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…A major difference in this study in relation to Reyes et al [18], one of the last articles published in the literature, is that they considered consecutive patients, without any exclusion (real life study), and on the other, the authors excluded patients with: concomitant surgeries, aortic surgery, reoperations, emergencies, high levels of creatinine, and patients with anemia BS<1.6 m 2 , as well as patients with a EuroSCORE> 10% and high risk of bleeding. This study showed 21% of patients with a EuroSCORE above that percentage, and the group that made use of CS, 6% of patients were operated on duration while using clopidogrel and a patient was being subjected to a fourth reoperation (fifth procedure).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…A major difference in this study in relation to Reyes et al [18], one of the last articles published in the literature, is that they considered consecutive patients, without any exclusion (real life study), and on the other, the authors excluded patients with: concomitant surgeries, aortic surgery, reoperations, emergencies, high levels of creatinine, and patients with anemia BS<1.6 m 2 , as well as patients with a EuroSCORE> 10% and high risk of bleeding. This study showed 21% of patients with a EuroSCORE above that percentage, and the group that made use of CS, 6% of patients were operated on duration while using clopidogrel and a patient was being subjected to a fourth reoperation (fifth procedure).…”
Section: Discussioncontrasting
confidence: 56%
“…This has been a path, with the highest incidence of use in patients for religious reasons and those who do not wish to make use of units of stored packed red blood cells (UPRBC). The use of this strategy varies from services to services in different continents, between 15% and 60% [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Niranjan et al [10] reported mean transfusion volumes and did not report the proportions of patients who received blood transfusion in the CS and non-CS groups; therefore, it was not included. Fifteen studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in the final analysis; of which, all reported RBC transfusion rate, and eleven [12,13,15-19,21-,24] reported platelet and FFP transfusion rates.…”
Section: Search Resultsmentioning
confidence: 99%
“…Fifteen studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] were identified [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1); all were included for the RBC transfusion outcome, and eleven [12,13,15-19,21-,24] were included for the platelet and FFP transfusion outcomes. All trials had at least two arms; two studies had three arms, and only one study used four arms (if CS was used in more than one arm, the results were combined for the CS arms).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%